Upaya Bank Syariah Indonesia (BSI) Cabang Sambas Dalam Meningkatkan Literasi Keuangan Masyarakat Tentang Perbankan Syariah dan Minat Menabung Nasabah - Munawir Munawir; Maskupah Maskupah (Cross-border, 2021)
Sharia Bank is a financial institution whose main business is collecting funds from the public and channeling it back to the community and other services in payment traffic and also the circulation of money whose operations are adjusted to the principles of Islamic Sharia based on the Al-Quran and Hadith. (M.Syafi'I Antonio 1971: 1) Particularly with regard to the procedures for meritorious in Islam, in other words, in the practice of muamalat it is known that practices that are feared contain elements of usury to be filled with investment activities on the basis of proceeds and trade finance. The research approach that the researcher is doing is descriptive research with a qualitative approach. Qualitative research is a form of research that requires a reduction process that comes from observations, interview results, or a number of documents. These data will then be summarized and selected so that they can be included in the appropriate category. Impact on Indonesian Sharia Bank (BSI) Sambas Branch in Improving Public Financial Literacy Regarding Sharia Banking and Customers' Interest in Saving. In increasing public financial literacy about Islamic banking and customers' interest in saving, it is to increase public insight, knowledge and understanding of Islamic banking and its products and services, as well as to increase skills in using banking products and services as well as to increase public interest in using fundraising products and products. financing so that the number of customers and increase public understanding of Islamic banks that are truly in line with the Koran and hadiths.